Motor learning and performance : from principles to application. - Lee, Timothy Donald, 1955-; Schmidt, Richard A. (Richard Allen), 1941-2015 (Human Kinetics, 2026)
'Motor Learning and Performance', seventh edition, constructs a conceptual model of factors that influence motor performance, outlines how motor skills are acquired and retained with practice, and describes how to apply those concepts to a variety of real-world settings.